"اثر الرسومات اليدوية في تنمية مهارات التعبير الفني لدي طلاب المرحلة الأساسية " (Comprehensive Journal of Science, 2026)
This study explores the role of hand drawing s In enhancing artistic expression among . Primary school  students . Using a descriptive- Analytical  approach , The study  highlights how  manual drawing activities can develop creative               Thinking , visual expression Thinking , visual expression, and self- confidence.  The findings support integrating hand Drawings into art educating to improve  Expression skills and encourage individuality .